Cooling performance analysis of nanofluid assisted novel photovoltaic thermoelectric air conditioner for energy efficient buildings - Bakthavatchalam, B. (Elsevier Ltd, 2022)
Carbon emissions and excessive power usage are addressed by applying thermoelectric cooling, which benefits from its ability to be portable, economical, and reliable. However, a conventional thermoelectric air conditioner's coefficient of performance (COP) is much less due to the sustained heat generated on the thermoelectric module's hot side. This work presents a novel idea of utilizing a nanofluid cooled radiator as an external cooling jacket around the thermoelectric module's hot side to enhance the heat transfer rate of thermoelectric air conditioners. In this research, the performance of a newly designed thermoelectric air conditioner (TEAC) powered by photovoltaic systems (PV) installed in a residential building is analyzed using nanofluid as a coolant. Furthermore, by supplying different input currents (2-6A), the cooling characteristics and performance of the newly designed nanofluid assisted thermoelectric air conditioner (NTEAC) system were experimentally studied in a test room of 25.6 m3 volume in Malaysia's tropical climate. The system's best performance was at 6A, with a maximum temperature drop of 4.9 Â°C, a cooling capacity of 571 W, and a coefficient of performance of 1.27. In addition, the NTEAC system showed an energy saving of 67 and CO2 emission mitigation of 76 when compared with a conventional split air conditioner. Thus, an alternative to the traditional air conditioning system was developed from this research, which is Freon free. This system is expected to consume less energy and emit less CO2 for the tropical climatic conditions. Â© 2022 Elsevier Ltd